Implant-supported prosthetic rehabilitation after Ameloblastomas treatment: a systematic review - Mario Alberto Alarcón-Sánchez; Julieta Sarai Becerra-Ruíz; Lazar Yessayan; Seyed Ali Mosaddad; Artak Heboyan (BMC, 2023)
Abstract Background Ameloblastoma (AM), the benign counterpart of ameloblastic carcinoma, is a benign odontogenic tumor of epithelial origin, naturally aggressive, with unlimited growth potential and a high tendency to relapse if not adequately removed. Patients with AM treated surgically can benefit from dental implant therapy, promoting oral rehabilitation and improving their quality of life. The present study aimed to determine the survival rate of dental implants placed after surgical treatment of patients affected by AM. In addition, there were two secondary objectives: 1) To evaluate which dental implant loading protocols are most frequently used and 2) To determine the type of prosthetic restoration most commonly used in these patients. Methods The Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines were followed during the study. Searches were performed in three databases (PubMed/MEDLINE, Scopus, and Google Scholar) until November 2023. Additionally, the electronic search was enriched by an iterative hand search of journals related to oral pathology and medicine, maxillofacial surgery, and oral prosthodontics and implantology. Only reports and case series in English from January 2003 to date were included. The Joanna Briggs Institute tool (JBI-Case Reports/Case Series) was used for the study quality assessment. Results The total number of patients and implants studied were 64 and 271, respectively, all with surgically treated AM. The patient's ages ranged from 8 to 79 years, with a mean (SD) age of 37.3 ± 16.4. Fifty-three percent were male and 47% were female. The range of follow-up duration was 1 to 22 years. An implant survival/success rate of 98.1% was reported. In addition, most of them were conventionally loaded (38.3%). Hybrid implant-supported fixed dentures were the most commonly used by prosthodontists (53%). Conclusions Oral rehabilitation with dental implants inserted in free flaps for orofacial reconstruction in surgically treated patients with AM can be considered a safe and successful treatment modality.